Angle-resolved Auger spectroscopy of K-shell ionized molecules. Issue 15 (January 2020) - Fuchs, S; Paul, D; Buhr, T; Ricz, S; Schippers, S
Synopsis: We report on measured oxygen K-LL Auger spectra induced by 1.5-keV electron impact on O2, CO2, and N2 O gaseous targets. An ESA-22-type electron spectrometer was employed which is capable of simultaneous energy and angular analysis covering a polar angular range of 15° to 345°. The measurements were carried out in preparation for future experiments with more complex chiral molecular targets and a spin-polarized electron source. The present experimental data are compared with results from earlier experimental studies.